Comparison of Oral and Intranasal Midazolam/Ketamine Sedation in 3-6-year-old Uncooperative Dental Patients - Fallahinejad Ghajari, Masoud (J Dent Res Dent Clin Dent Prospects, 2015)
Background and aims. There are several known sedative drugs, with midazolam and ketamine being the most commonly used drugs in children. The aim of this study was to compare the effect of intranasal and oral midazolam plus ketamine in children with high levels of dental anxiety. Materials and methods.A crossover double-blind clinical trial was conducted on 23 uncooperative children aged 3-6 (negative or definitely negative by Frankel scale), who required at least two similar dental treatment visits. Cases were randomly given ketamine (10 mg/kg) and midazolam (0.5 mg/kg) through oral or intranasal routes in each visit. The sedative efficacy of the agents was assessed by an overall success rate judged by two independent pediatric dentists based on Houpt’s scale for sedation. Data analysis was carried out using Wilcoxon test and paired t-test. Results. Intranasal administration was more effective in reduction of crying and movement during dental procedures compared to oral sedation (P<0.05). Overall behavior control was scored higher in nasal compared to oral routes at the time of LA injection and after 15 minutes (P<0.05). The difference was found to be statistically significant at the start and during treatment. However, the difference was no longer significant after 30 minutes, with the vital signs remaining within physiological limits. Recovery time was longer in the intranasal group (P<0.001) with a more sleepy face (P=0.004). Conclusion.. Intranasal midazolam/ketamine combination was more satisfactory and effective than the oral route when sedating uncooperative children.